Structural perspectives on recent breakthrough efforts toward direct drugging of RAS and acquired resistance - Lokhandwala, Jameela; Smalley, Tracess B.; Tran, Timothy H. (Frontiers in Oncology, 2024)
The Kirsten rat sarcoma viral oncoprotein homolog (KRAS) is currently a primary focus of oncologists and translational scientists, driven by exciting results with KRAS-targeted therapies for non-small cell lung cancer (NSCLC) patients. While KRAS mutations continue to drive high cancer diagnosis and death, researchers have developed unique strategies to target KRAS variations. Having been investigated over the past 40 years and considered “undruggable” due to the lack of pharmacological binding pockets, recent breakthroughs and accelerated FDA approval of the first covalent inhibitors targeting KRASG12C, have largely sparked further drug development. Small molecule development has targeted the previously identified primary location alterations such as G12, G13, Q61, and expanded to address the emerging secondary mutations and acquired resistance. Of interest, the non-covalent KRASG12D targeting inhibitor MRTX-1133 has shown promising results in humanized pancreatic cancer mouse models and is seemingly making its way from bench to bedside. While this manuscript was under review a novel class of first covalent inhibitors specific for G12D was published, These so-called malolactones can crosslink both GDP and GTP bound forms of G12D. Inhibition of the latter state suppressed downstream signaling and cancer cell proliferation in vitro and in mouse xenografts. Moreover, a non-covalent pan-KRAS inhibitor, BI-2865, reduced tumor proliferation in cell lines and mouse models. Finally, the next generation of KRAS mutant-specific and pan-RAS tri-complex inhibitors have revolutionized RAS drug discovery. This review will give a structural biology perspective on the current generation of KRAS inhibitors through the lens of emerging secondary mutations and acquired resistance.